A SYSTEMATIC MAPPING REVIEW OF IN-VITRO AND IN-VIVO EVIDENCES EXPLORING THE ROLE OF STRAIN-SPECIFIC PROBIOTIC BIFIDOBACTERIUM LONGUM W11 (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The gut microbiome has a significant role in overall well-being. Various probiotics are currently used for the improvement of the gut microbiome; the current scoping review aimed to critically examine the effectiveness of Bifidobacterium longum W11 in healthy and disease states. A thorough search of the literature was done in three scientific databases (PubMed, ScienceDirect, and Google Scholar) to identify and retrieve in-vitro, pre-clinical, and clinical evidence that evaluated the effect of B. longum W11 probiotic. Two independent reviewers identified and screened articles, published from 2000 to 2023 from the databases. Data from eligible studies were extracted, compiled, critically evaluated for scientific strength, and presented in this scoping review. Initially, 663 articles were identified and after a complete screening and evaluation process, twenty-one articles (eight in-vitro and animal studies; thirteen clinical studies) were included. Pre-clinical data suggest that B. longum W11 can withstand the severe gastrointestinal environment and colonize the intestinal epithelial cells to a significant degree. Due to the presence of a specific EPS cluster gene, B. longum W11 is capable of producing unique exopolysaccharides that might be responsible for the adhesion and functional capabilities of B. longum W11. Additionally, the specific mutation in the rpoB gene confers the B. longum W11 resistance to all rifamycin derivatives (including rifaximin). Clinical studies involving individuals with constipation and irritable bowel syndrome have shown that B. longum W11 supplementation significantly improves the overall quality of life and reduces the severity of symptoms. Furthermore, B. longum W11 was found to be effective in minimal hepatic encephalopathy and active celiac disease conditions. Due to the antibiotic resistance, the simultaneous use of rifaximin and B. longum W11 in patients with uncomplicated diverticular disease condition resulted in greater improvement in various symptoms compared to rifaximin supplementation alone. These data suggest that B. longum W11 is a potential probiotic that can be administered along with antibiotics in various gastrointestinal disease conditions. This evidence suggests that B. longum W11 is a promising probiotic with potential applications in various functional and inflammatory GI-related complications. Further clinical studies and stringent systematic reviews are needed to strengthen the outcomes of the current study.